PENGABDIAN KEPADA MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN) DI DESA PENARI PASURUAN JAWA TIMUR - Alfan Nuril Hidayat; Mazroatus Saadah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Abstract: Real Work Lecture (KKN) activities in Penari Village, Pasuruan, East Java, were carried out by students at Bhayangkara University, Jakarta Raya as a form of service to the community. This program lasts for one month with the aim of increasing public awareness of various aspects, such as education, health, environment and socio-culture. Various activities were carried out, including Takbiran Bersama and Coloring Competitions for children, which aimed to strengthen religious values, strengthen social relationships, and develop creativity and fine motor skills in children. The approach used in implementing this KKN is a participatory method, where students collaborate with the community to design and implement programs that suit local needs. Takbiran Bersama activities help strengthen togetherness and religious traditions, while coloring competitions provide fun education for children and support their psychological and social development. The results of this KKN activity show a positive impact, both in terms of increasing community participation in social activities and strengthening relationships between universities and village communities. The programs implemented are also able to contribute to increasing environmental awareness and community life skills. Overall, this KKN succeeded in achieving its main objective, namely helping to develop village communities and providing students with practical experience in applying their knowledge in the field.